Enhanced Thermal, Mechanical, and Electrical Properties of Epoxy Composites Reinforced with CdS/MWCNT Nanohybrids Synthesized via Hydrothermal Method - Şahal, Hakan; Aydoğmuş, Ercan (My University, 2025)
In this research, the effects of incorporating a hybrid nanocomposite consisting of cadmium sulfide (CdS) nanoparticles and multi-walled carbon nanotubes (MWCNTs) synthesized by hydrothermal method into an epoxy resin system on the bulk density, Shore D hardness, thermal conductivity coefficient, thermal stability, and dielectric properties have been investigated. In addition, the structural and physical properties of these nanocomposites aimed to determine their potential applications as lightweight and thermal insulation materials. The study included synthesizing CdS/MWCNT nanohybrid structures using CdCl?•H?O and Na?S?O?•5H?O precursors under specific time and concentration parameters. Then, these nanohybrids were integrated into the epoxy matrix to form innovative composite materials. The prepared composite samples were characterized using various methods to evaluate their mechanical, thermal, structural, and electrical properties. Techniques such as tensile tests, Shore D hardness measurements, microscopy, Fourier transform infrared spectroscopy (FT-IR), thermal conductivity, and dielectric measurements were used. The findings revealed that incorporating certain amounts of CdS/MWCNT nanohybrids significantly affected the density, hardness, thermal conductivity, mechanical strength, and dielectric properties of epoxy composites. In particular, the high surface area and effective distribution of CdS/MWCNT nanohybrid increased the mechanical strength and improved the thermal and electrical conductivities. The bulk density measured as 1133.5 kg/m³ in the first experimental group reached 1145.1 kg/m³, showing a steady increase until the 5th group. Shore D hardness measurements, which were initially measured as 77.6, increased to 79.8 in the last experimental group with the addition of nanohybrid structures. The thermal conductivity measured as 0.112 W/m•K in the first experimental group reached 0.136 W/m•K in the last group. Dielectric measurements showed that the dielectric coefficient increased from 3.86 in the initial sample to 5.67 in the nanoparticle-reinforced epoxy composites, indicating that the additive significantly improved the electrical properties, leading to a higher dielectric constant and enhanced energy storage potential. Microscopy images confirmed the homogeneous distribution of the nanohybrid within the epoxy matrix and strong interfacial interactions. FT-IR analysis confirmed the chemical bonds present in the hybrid composite structure. These results highlight the significant potential of incorporating CdS/MWCNT nanohybrid structures into epoxy composites to develop functional materials with advanced technological applications. This comprehensive study provides valuable insights into nanocomposite technology and highlights the promising role of CdS and MWCNT-based hybrid systems in future material designs.
Keywords: MWCNT; Thermal Conductivity; Hydrothermal method; Dielectric constant; Cadmium sulfide; Hybrid nanocomposite